1993
DOI: 10.1557/proc-297-821
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Performance of A-SiGe:H Solar Cells for Multi-Junction Cells

Abstract: The quality of a-SiGe:H film was improved by considering the effects of substrate temperature and deposition rate on film properties. Accurate measurement of the optical gap and the film composition of Si, Ge and H made it possible to formulate the optical gap using a linear function of bonded H content (CH) and Ge content (CGE). It was found for the first time that, when the optical gap is fixed to a certain value, the optimum compositions of CHAand CGe exist for high-quality a-SiGe:H. Based on these, we obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This observation is in good agreement with the data reported by Maruyama et al 18 The growth rate for our a-SiGe:H alloys was always below 3 nm/min and therefore we can assume that the change in the optical gap at increased growth tem- peratures is not caused by the change of the Ge content in the films.…”
Section: Resultssupporting
confidence: 93%
“…This observation is in good agreement with the data reported by Maruyama et al 18 The growth rate for our a-SiGe:H alloys was always below 3 nm/min and therefore we can assume that the change in the optical gap at increased growth tem- peratures is not caused by the change of the Ge content in the films.…”
Section: Resultssupporting
confidence: 93%
“…The biased quantum efficiency serves as an important tool in the investigation of carrier collection losses in a-Si 1−x Ge x :H single-junction cells [15]. This approach would give us physical insight into the correlation among carrier collection, carrier generation, and bandgap grading width in the absorber.…”
Section: International Journal Of Photoenergymentioning
confidence: 99%
“…Guha et al have reported that the employment of bandgap graded layers in the absorber can facilitate carrier collection, strengthen the built-in electric field, and thus improve the cell efficiency [10]. Several groups have reported the optimized bandgap grading structure in a-Si 1−x Ge x :H absorber with a-Si:H n-layer through numerical simulation approaches [11][12][13][14][15][16]. However, there are still possibilities in designing the graded bandgap structure.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly two types of profiles have been investigated. The U-shape grading of the i-layer [1] leads to a better performance of the cell, by reducing the recombination at the p/i and i/n interfaces. The V-shape grading of the i-layer [2,3] reduces the trapped charge concentration and lowers the recombination losses by diminishing the average amount of Ge alloying.…”
Section: Introductionmentioning
confidence: 99%